Patokan harga nilai jual objek pajak di kota Banda Aceh: Analisis perspektif mekanisme harga dalam Islam - Nilam Sari; Ridha Jadidah (IAIN Langsa, 2020)
Sale Value of Taxable Object (SVTO) is the averageprice obtained from the sale and purchase transactions that occur naturally, and when there is no buying or selling, then SVTO determined through a price comparison with other similar objects or substitution Although in operation, SVTO was not used directly in the case of land purchase, but sometimes the processes and mechanisms involved may violate the concept of buying and selling in Islam, such as the element of coercion and fair price. The researcher was intended to examine on how the processes and mechanisms of release of land by the government of Banda Aceh and how calculations of SVTO to the land purchase and its suitability with the Islamic price mechanism, the researcher conducted interviews with staﬀ of UPTD PBB DPKAD of Banda Aceh. The descriptive analysis method was used in this, and the collecting data were analyzed qualitatively. The results showed that in the process and mechanism of release of land, the government does not use SVTO which is based on existing provisions. However, its implementation was done by estimating the real price of the object purchased. Not only that, but also it also referred to other possibilities such as land location. In general, the implementation is legal. The author suggests government to put more emphasis on adequate compensation to the community so that it can cover the costs of looking for a house/new land, the cost of moving, survival, and so on.